Employee Opinion Survey Sebagai Sarana Untuk Mengidentifikasi Kepuasan Kerja Karyawan Menuju Kesejahteraan Psikologis di Tempat Kerja - Wustari L. Mangundjaya (CV. ULIL ALBAB CORP, 2024)
Every organization would like their talented employees to be loyal, happy, comfort in their job. This condition can be achieved only if the employees satisfied with their companies. To identify whether employees feeling satisfied in their job, organization has to conduct employee opinion survey, with the objectives to identify the profile of employee satisfaction. This study was conducted at one bank in Indonesia with 3047 respondents. Results showed that in general employees have quite satisfied with the company, with rank of satisfaction as follows: 1) with the job, 2) with the climate of work, 3) opportunities for development, and 4) relationship between superior and subordinates. This result is in line with the concept of workplace well-being that mostly about psychological aspects.